On Nadia Urbinati, Democracy Disfigured: Opinion, Truth, and the People and Pierre Rosanvallon, The Society of Equals - Bashkina, Olga (Stasis, 2016)
Book review: Nadia Urbinati, Democracy Disfigured: Opinion, Truth, and the People Cambridge, MA: Harvard University Press, 2014, 320pp., ISBN 978-0674725133 Pierre Rosanvallon, The Society of Equals Cambridge, MA: Harvard University Press, 2013, 384pp., ISBN 978-0674724594